A polyethylene-high proportion hydroxyapatite implant and its investigation in vivo - Sarsilmaz, F.; Orhan, N.; Unsaldi, E.; Durmus, A. S.; Colakoglu, N. (Wroclaw Univ Technology, 2007)
An implant from hydroxyapatite and polyethylene (HA+PE) composite was investigated for the usability in large bone defects. With this aim, the implants were manufactured in blocks by hot compacting the mixture of 80% HA and 20% PE weight ratio. Powders were machined in a lathe in the dimensions of diaphysis of the radius of the mongrel dogs. Then a defect, 1.5 cm in length, was made in the diaphysis of the radius with an operation performed under general anaesthesia in 16 healthy mongrel dogs. The defects were filled with implant as a block. The dogs were observed radiologically in 15-day intervals and examined clinically in certain intervals. The bone samples were taken out from four dogs for the histopatological examinations at the end of the 2nd, 4th, 6th and 12th months, respectively. Clinical examinations indicated the occurrence of slight lameness in all cases at the first month of experiment, but lameness completely disappeared in a further examination. Progressive resorption and new bone formation began in the implants from the first month, but complete resorption was not observed in any case at the end of 12-month period. SEM and optical microscope examinations revealed fibroblast cell with its clear cytoplasmic extensions and osteoblast cells in endosteum in the inner region. Bone formation increasing and extending to the pores of implant in time and blood vessels with lamellar structure and Haversian system were observed. As a result, it was indicated that HA+PE composite implants could be applied with confidence and are useful in treatment of large bone defects in long bone of dogs.
Keywords: hydroxyapatite; polyethylene; implant; bone defect